“AN OGRE AT OUR DOORSTEP” – CAN THE RUSSIAN THREAT UNITE EUROPE? - Preradović, Nikola (Political Review, 2026)
When French President Emmanuel Macron extravagantly compared Russian leader Vladimir Putin and his policies to an evil mythological creature, an “ogre on Europe’s doorstep,” he reflected the perception, prevalent in many European capitals, of an aggressive and expansionist Russia that threatens the security of the entire continent. The idea of ​​an acute Russian threat has become the guiding star of the accelerated militarization of European Union (EU) member states and attempts to improve common defense capabilities. The initial impetus for such a development was the war in Ukraine, which was presented by advocates of greater integration and autonomy in the defense sector as a potential turning point for European security, but also as a kind of Copernican twist that would bring the long-standing fantasy of European strategic autonomy, independent of the changing priorities of the United States, closer to reality. The aim of this paper is to reexamine the assumption about the role of the war in Ukraine in two main ways. First, it questions the very credibility of the idea of ​​a Russian threat that threatens the entire continent. Second, it points out that Moscow's actions, due to different perceptions of the threat and divergent interests, do not cause the same degree of concern among all EU states. The main hypothesis of the paper is that emphasizing the Russian threat is insufficient to establish a cohesive, unified approach among EU states to defense and security issues. Relying on the assumptions of the balance of threat theory to inform decisions on balancing and balancing interests to reflect divergent interests within the EU, the paper points out the challenges faced by a community of sovereign states when it must behave as a great power in an anarchic international system.
Keywords: Russia; European Union; war in Ukraine; defense; threat; national interest